Procedure for Drawing Up And Presenting Accounting Policies In Non-State Non Profit Organizations - Turaev, A.N.; Adilova, G.Dj. (International Journal of Psychosocial Rehabilitation, 2020)
In this article gives methodological recommendations on the formation of accounting policy in the non-state non-profit organizations (NSNPO) and disclosed the practical aspects of their implementation.